Application of Project-Based Learning with Fan Material to Increase Learning Motivation in Class X IPA 3 SMA Lab School USK Students - Faudiah, Nurul; Dewi, Rosmala; Indani; Fadhilah; Nurbaiti; Umaiya, Anisa (International Journal of Applied Educational Research (IJAER), 2024)
Learning motivation is an absolute requirement for learning and has an importance in providing enthusiasm for learning, for this reason, efforts are needed by teachers to foster student learning motivation. One of them is by applying the Project Based Learning model. The purpose of this study was to apply the Project Based Learning learning model in an effort to increase student learning motivation in entrepreneurship workshop subjects with gold thread embroidery fan material and to determine the increase in student learning motivation in class X IPA 3 SMA Lab School Unsyiah. The research sample was students of class X IPA 3 SMA Lab School Unsyiah with 35 students. Data collection was obtained through observation of learning activities and tests. The results of the study obtained learning activities in cycle I with an average value of 4.32 (86%) including in the category of excellent, for the results of learning motivation in cycle I with an average value of 91.14% has reached the set target of 80%, then for the results of the final post-test of the cycle I with individual completeness (86%) has reached the completeness criteria of 80%. The research conclusion is that the application of the Project Based Learning learning model can increase student learning motivation. Therefore, the application of Project Based Learning can be applied to other learning.